Implementasi Pengelolaan Dana Zakat Sebagai Corporate Social Responsibility Di Lembaga Keuangan Syariah (Studi Kasus BPRS Bhakti Sumekar Sumenep) - Irmawati; Evi Malia (Jurnal Penelitian Teori dan Terapan Akuntansi (PETA), 2022)
The purpose of this study was to determine how the management of zakat funds as corporate social responsibility. The type of research method used is descriptive qualitative. With data collection methods using observation, interviews, and documentation. The results of this study indicate that BPRS Bhakti Sumekar distributes CSR funds from zakat and benevolence funds. BPRS Bhakti Sumekar distributes its own corporate social funds (CSR) with various activity programs, namely: education, health, economic empowerment, compensation, calamities and disasters, as well da’wah and construction of religious facilities. CSR distribution has been clearly presented, but BPRS has not allocated CSR funds equal to 2% of company profits because BPRS Bhakti Sumekar considers that CSR is the same as ZIS (zakat, infaq, alms). According to the laws and regulations there is a difference between the two, namely that companies both have an obligation to carry out their social responsibilities and to pay their zakat. Besides that there is a difference in the level (amount) of funds that must be disbursed.